Clinical Features of Four West Nile Virus Cases and Its Molecular Characterization from a South Indian Tertiary Care Hospital. (16th July 2020) - Mammen, Shoba; Nair, Aiswarya; Kumar, Santhosh; Zonderveni, Zayina; Prabhakar, A. T.; Vijay Prakash, Turaka; Aaron, Sanjith; Alexander, Mathew; Zachariah, Anand; Abraham, Asha Mary
Abstract : West Nile virus (WNV) is currently a significant reemerging virus of the 21st century. It belongs to the family Flaviviridae and genus Flavivirus . Although it is primarily transmitted by the Culex spp of mosquitoes, other routes of transmission are also well defined. Of eight lineages described, Lineage 1a has been reported from many parts of South India and is known to cause neuroinvasive illness. Many tests and serological techniques have been described to diagnose WNV infection such as complement fixation, neutralization, heamagglutination inhibition, ELISA, and PCR for molecular confirmation. The latter far outweighs the limitations inherent in the other tests. WNV infection is being reported from Vellore for the first time after 1968. This paper aims to describe four cases of WNV infection causing central nervous system manifestations with its molecular characterization. West Nile virus infection was diagnosed with the available molecular techniques such as PCR and sequencing, which emphasizes the need for considering West Nile virus in the differential diagnosis of acute meningoencephalitis and the wider availability of molecular diagnostic tests.